2018
DOI: 10.1177/0003319718799967
|View full text |Cite
|
Sign up to set email alerts
|

Perirenal Fat: A Unique Fat Pad and Potential Target for Cardiovascular Disease

Abstract: Although visceral obesity is recognized as a risk factor for cardiovascular diseases (CVDs), the efficacy of omental fat removal in CVD treatment is still controversial. There is a need to identify other visceral fat depots for CVD management. This review aims to provide a summary on perirenal fat as an important risk factor for CVD. Studies on epidemiology, anatomy, and function of perirenal fat were reviewed. Observational studies in humans suggest that excessive perirenal fat increases the risk of hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
106
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 103 publications
0
106
0
1
Order By: Relevance
“…Intrauterine programming of adiposity by thyroid hormones has implications for adult insulin sensitivity and metabolic disease (17). Cross talk between adipose tissue, especially PAT (18), liver, and skeletal muscle may be mediated by adiposederived factors, such as free fatty acids and adipocytokines. In adult humans, PAT thickness has been correlated with increased risk of conditions, including hypertension, fatty liver, and coronary heart disease (18).…”
Section: Introductionmentioning
confidence: 99%
“…Intrauterine programming of adiposity by thyroid hormones has implications for adult insulin sensitivity and metabolic disease (17). Cross talk between adipose tissue, especially PAT (18), liver, and skeletal muscle may be mediated by adiposederived factors, such as free fatty acids and adipocytokines. In adult humans, PAT thickness has been correlated with increased risk of conditions, including hypertension, fatty liver, and coronary heart disease (18).…”
Section: Introductionmentioning
confidence: 99%
“…Fourthly, adipose tissue can be accumulated in depots other than VF ectopic fat, for example, as perirenal, perivascular, pericardial and intramuscular fat, and/or fat infiltrating the liver or pancreas. These conceivably might produce both local and systemic metabolic effects similar to VF . DXA does not differentiate these other regions of ectopic fat and includes them with TBF, subcutaneous fat, or VF.…”
Section: Discussionmentioning
confidence: 99%
“…It has complete system of blood supply, lymph fluid drainage, and innervation [6]. Several studies have reported the close relationship between para-and perirenal fat and cardiovascular diseases, including atherosclerosis, blood pressure, endothelial damage [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%